Ruidos, colores infinitos. - Herrera, Georgina (Afro-Hispanic Review)
Presents the poem "Ruidos, colores infinitos," by Georgina Herrera, translated by Jorge Brash. First Line: "Eso que oyes, es la tojosa" decía; Last Line: colores infinitos.